New Climate Data Builds Agricultural Resilience in a Changing Climate - Jay, A.; Fiondella, Francesco; Hansen, James; Coffey, Kevin (2015)
Understanding and predicting Ethiopia’s complex climate at multiple scales with enough detail and certainty to make critical food-security decisions at local levels requires timely, quality assured weather, climate and agricultural data at a high spatial and temporal resolution. The Enhancing National Climate Services (ENACTS) initiative delivers robust climate data, targeted information products and training specifically relevant to the needs of farmers and food security decision makers at multiple levels, empowering a diverse range of actors to use past, present and future climate information in agriculture and food securityrelated response actions with confidence.